DAMPAK PELESTARIAN HUTAN MANGROVE BAGI EKOSISTEM DAN MASYARAKAT DI DESA LONTAR - Lilis, Lilis; Wulandari, Gustini; Wibowo, Zidan; Sulastri, Lulu Andriani; Tristanti, Nova; Febrianti, Febri (Gapenas Publisher, 2024)
Indonesia is a country with many islands, making Indonesia one of the maritime countries in the world. Indonesia also has many forests spread across all the islands in Indonesia. A forest is a place that grows various types of plants and various types of animals in it. Forests in Indonesia are so vast that they are the largest source of oxygen production in the world. One of the problems of island countries is abrasion. Abrasion is a process that causes the erosion of the shoreline caused by waves and sea currents. Abrasion can be prevented, one way is by planting mangrove trees around the shoreline to reduce the occurrence of abrasion. Mangrove forests are forests located on the coast of Lontar and in estuaries with brackish water. The mangrove forest ecosystem is one of the most productive and unique ecosystems which functions to protect coastal areas from various disturbances, as well as providing habitat for various animal species. Mangrove forests not only function physically, chemically and biologically to maintain the balance of the ecosystem, but also have social, economic and cultural functions for the coastal communities of Lontar villages who inhabit them. As one of the most productive ecosystems, mangrove forests cannot be separated from being used for human benefit